PETTLEP IMAGERY COMPONENTS AND PHYSICAL TRAINING ACTIVITIES CONSIDER AS PRACTICE IN MIND (PIM): A COMBINATION OF COMPREHENSIVE PHYSICAL TRAINING PROGRAM FOR FOOTBALL PLAYERS. - Mohd Firdaus Mohd Nasir; Jamatul Shahidah Shaari; Siti Amaliya Mohd Radyi; Nur Ida Fatihah Che Shalifullizam (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
PETTLEP imagery components consist of the Physical, Environment, Timing, Task, Learning, Emotion and perspective of each player in that team. Meanwhile, Physical Training usually focuses on speed and strength training, as well as endurance training, and may involve interval training, circuit training, fartlek training, and plyometric training. However, the training approach will depend on football player; they may employ a variety of various methods to improve all aspects of their performance. So now, Practice in Mind (PIM) Training is a program that combines imagery and physical training which consists of seven PETTLEP components. Other than motivation, visual, and kinesthetic directions, the imagery material in the PIM training program includes the facilitative imagery direction and stimulus to react to the propositions. Hence to infer that imagery in sports performance is particularly effective in settings where practical restrictions impede physical training, such as biomechanical stiffness, weak physical strength, weariness, injury risk, and restricted access to equipment. In fact, imagery therapies have been shown to increase strength tasks when combined with physical training.